EnviBUILD 2014 : selected, peer reviewed papers from the 9th International enviBUILD 2014 Conference, September 18-19, 2014, Brno, Czech Republic - Kalousek, Miloš; Čekon, Miroslav (Advanced materials research, 2014)
Collection of selected, peer reviewed papers from the 9th International enviBUILD 2014 Conference, September 18-19, 2014, Brno, Czech Republic. The 99 papers are grouped as follows: Chapter 1: Building Materials and Components, Chapter 2: Energy Performance of Buildings, Chapter 3: Retrofitting and Revitalization of Buildings, Chapter 4: Sustainable Building and Environmental Assessments, Chapter 5: Hygrothermal Performance of Buildings, Chapter 6: Indoor Climate, Thermal Comfort and Ventilation, Chapter 7: Daylighting and Insolation, Chapter 8: Acoustics and Noise Protection. Keyword: Building Components, Building materials, Energy performance, Thermal Performance, Retrofitting, Building Renovations, Sustainable Building, Environmental Assessment, Building Physics, Thermal Comfort, Ventilation, Daylighting, Insolation, Acoustics, Noise Protection The conference focused on specific issue related to buildings and the environment especially in Central Europe, and provided an opportunity to discuss recent findings in the scientific and academic community. The 98 papers cover building materials and components the energy performance of buildings; retrofitting and revitalizing buildings; sustainable building and environmental assessments; the hygrothermal performance of buildings; indoor climate, thermal comfort, and ventilation; daylighting and insolation; and acoustics and noise protection. -- Built environment-- Construction-- Materials science.